Clinical Characteristics of Deformities in Leprosy Patients Attending a Tertiary Care Hospital (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: Disability assessment in leprosy patients is a very important factor in the evaluation of the effectiveness of a leprosy elimination program. Little information exists on deformities of leprosy in Bangladesh. To describe the pattern and prevalence of deformities in leprosy patients after leprosy has been declared eliminated in Bangladesh in 1998.Materials and methods: A descriptive retrospective cross-sectional study was carried out in Chittagong Medical College Hospital using the registered records of patients between the periods 2004 and 2013. No of respondence was 670.Results: Out of 670 leprosy patients 213 (31.79%) had a deformity. The prevalence of deformity was for grade 1: 92 (43.20%) for the grade 2: 121 (56.80%). Among the patients with deformity males 144 (67.60%) out numbered females 69 (32.40%). Four age groups were considered. The calculated age-specific cumulative detection rates showed the highest case detection in > 40 years group at 81 (38.02%). The rate of children (